Konflikt z perspektywy erystyki i eutoryki - Korwin-Piotrowska, Dorota (Tematy i Konteksty, 2017)
The article analyzes conflict as a phenomenon connected with persuasion – close to disputes or quarrels, yet not identical with them. The background for the considerations encompasses works from various fields: sociology, linguistics, philosophy, and psychology, but rhetoric remains in the very center. The author characterizes its part dealing with absolute winning in disputes, i.e. eristic, and it presents a counterbalance to it and to the agonistic attitude. This complement is eutoric (author’s own term) as a branch of rhetoric which concentrates on positive communication based on mutual listening, empathy and a constructive dialogue, which favors prevention of conflicts, or possibly resolving them. Eutoric has its source in philosophy of dialogue, pragmalinguistics, psychology of persuasion, as well as in the theory and practice connected with mediations and negotiations.